Question
upstudy study bank question image url

1 Solve for \( x \) and \( y \) in the f a \( 3 y+x=2 \) \( y^{2}+x=x y+y \) d \( y+13-6 x=0 \)

Ask by Morgan Santiago. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

There is no solution for the given system of equations.

Solution

Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}3y+x=2\\y^{2}+x=xy+y\\y+13-6x=0\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=2-3y\\y^{2}+x=xy+y\\y+13-6x=0\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}y^{2}+2-3y=\left(2-3y\right)y+y\\y+13-6\left(2-3y\right)=0\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}y^{2}+2-3y=3y-3y^{2}\\19y+1=0\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}y=1\cup y=\frac{1}{2}\\19y+1=0\end{array}\right.\) - step5: Evaluate: \(\left\{ \begin{array}{l}y=1\\19y+1=0\end{array}\right.\cup \left\{ \begin{array}{l}y=\frac{1}{2}\\19y+1=0\end{array}\right.\) - step6: Calculate: \(y \in \varnothing \cup \left\{ \begin{array}{l}y=\frac{1}{2}\\19y+1=0\end{array}\right.\) - step7: Calculate: \(y \in \varnothing \cup y \in \varnothing \) - step8: Rearrange the terms: \(y \in \varnothing \) - step9: Calculate: \(\left\{ \begin{array}{l}x \in \varnothing \\y \in \varnothing \end{array}\right.\) - step10: Rewrite: \((x, y) \in \varnothing\) The system of equations provided is: 1. \( 3y + x = 2 \) 2. \( y^2 + x = xy + y \) 3. \( y + 13 - 6x = 0 \) After solving this system, we find that there is **no solution**. This means that the equations are inconsistent and do not intersect at any point in the coordinate plane.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To solve the system of equations given: 1. \( 3y + x = 2 \) 2. \( y^2 + x = xy + y \) 3. \( y + 13 - 6x = 0 \) Let's rewrite the equations for clarity: 1. \( x = 2 - 3y \) (from equation 1) 2. Rearranging equation 2 gives \( y^2 + x - xy - y = 0 \). 3. Rearranging equation 3 gives \( x = \frac{y + 13}{6} \). You can substitute \( x \) from the first equation into the second and solve, ultimately working through the algebraic manipulations to find specific values for \( x \) and \( y \). Additionally, with the third equation, you can further validate your solution. Happy solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy